Molecular detection of cellular prion protein in brain tissues of black bengal goats in Bangladesh - Nasrin Sultana; Mohd Zahirul Islam Khan; Emdadul Haque Choudhury; Md Rafiqul Islam
The cellular prion protein (PrPC) is a membrane-bound glycoprotein mainly present in the central nervous system which is necessary for the establishment and further evolution of prion disease in human and animals. The aim of the present study was to investigate the PrPC protein in brain tissues of black Bengal goat. Fifteen brain tissues were collected from different slaughter houses of three districts (Mymensingh, Manikgonj and Netrokona) of Bangladesh during January to February, 2011. The PrPC protein was detected in the brain tissues of black Bengal goats using polymerase chain reaction. The result showed all positive (100%) of the amplified samples. The standardized PCR could be used for detection of PrPC protein in different tissues of animals and humans. Sequencing of PrP gene in the black Bengal goats for the risk assessment of scrapie is needed for further study. To our knowledge, detection of PrPC protein in the brain tissues of indigenous goats is the first time in Bangladesh